Measurement of the ZZ cross-section in e(+)e(-) interactions at 183-189 GeV - Abreu, P; Adam, W; Adye, T; Adzic, P; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; et al. (2001)
Measurements of on-shell ZZ production are described, using data collected by DELPHI in 1997 and 1998, at centre-of-mass energies √s = 182.6 GeV and 188.6 GeV, respectively. Results obtained in each of the final states qq̄qq̄, μ+μ-qq̄, e+e-qq̄, vv̄qq̄ l+l-l+l-, and vv̄l+l- are presented. The measured cross-sections for on-shell ZZ production via the tree-level doubly-resonant graphs (NC02) are: σNC02 (182.6 GeV) = 0.38 ± 0.18 (stat) ± 0.04 (syst) pb, σNC02 (188.6 GeV) = 0.60±0.13 (stat) ±0.07 (syst) pb. They are consistent with the Standard Model expectations of 0.25 and 0.65 pb at each energy. © 2001 Elsevier Science B.V.